-(-a+b+b)+(b+b-1)=a-b-b+b+b-1
=a+ ((-b)+(-b)+b+b) -1
=a+0-1
=a-1
(b-c+6)-(7-a+b)+c=b-c+6-7+a-b+c
=b+(-c)+6+(-7)+a+(-b)+c
=(b+(-b)) + ((-c)+c) + a + (6+(-7))
=0+0+a+(-1)
=a-1
Vậy -(-a+b+b)+(b+b-1)=(b-c+6)-(7-a+b)+c
-(-a+b+b)+(b+b-1)=a-b-b+b+b-1
=a+ ((-b)+(-b)+b+b) -1
=a+0-1
=a-1
(b-c+6)-(7-a+b)+c=b-c+6-7+a-b+c
=b+(-c)+6+(-7)+a+(-b)+c
=(b+(-b)) + ((-c)+c) + a + (6+(-7))
=0+0+a+(-1)
=a-1
Vậy -(-a+b+b)+(b+b-1)=(b-c+6)-(7-a+b)+c
-(-a+b+b)+(b+b-1)=a-b-b+b+b-1
=a+ ((-b)+(-b)+b+b) -1
=a+0-1
=a-1
(b-c+6)-(7-a+b)+c=b-c+6-7+a-b+c
=b+(-c)+6+(-7)+a+(-b)+c
=(b+(-b)) + ((-c)+c) + a + (6+(-7))
=0+0+a+(-1)
=a-1
Vậy -(-a+b+b)+(b+b-1)=(b-c+6)-(7-a+b)+c